A Detailed Survey of the Parallel Mean Free Path of Solar Energetic Particle Protons and Electrons - Lang, J. T.; Strauss, R. D.; Engelbrecht, N. E.; van den Berg, J. P.; Dresing, N.; Ruffolo, D.; Bandyopadhyay, R. (IOP Publishing Ltd, 2025)
In this work, more than a dozen solar energetic particle (SEP) events are identified where the source region is magnetically well connected to at least one spacecraft at 1 au. The observed intensity-time profiles, for all available proton and electron energy channels, are compared to results computed using a numerical one-dimensional SEP transport model in order to derive the parallel mean free paths (pMFPs) as a function of energy (or rigidity) at 1 au. These inversion results are then compared to theoretical estimates of the pMFP, using observed turbulence quantities with observationally motivated variations as input. For protons, a very good comparison between inversion and theoretical results is obtained. It is shown that the observed inter-event variations in the inversion pMFP values can be explained by natural variations in the background turbulence values. For electrons, there is relatively good agreement with pMFPs derived assuming the damping model of dynamical turbulence, although the theoretical values are extremely sensitive to the details of the turbulence dissipation range, which themselves display a high level of variation.